Prescribing Pattern of Antihypertensive Drugs in Hypertensive Patient with Non-Insulin Dependent Diabetes Mellitus (Medical Forum Monthly, 2023)
Objective: The basic aim of the study is to find the prescribing pattern of antihypertensive drugs in hypertension patients with non-insulin dependent DM.Study Design: Prospective observational studyPlace and Duration of Study: This study was conducted at the Gulab Devi Hospital, Lahore from December 2022 to June 2023.Methods: A total of 220 patients were recruited for this study through a systematic sampling method. Inclusion criteria encompassed individuals aged 18 years and older, diagnosed with both hypertension and non-insulin-dependent diabetes mellitus (NIDDM), as confirmed by their medical records.Results: Data was collected from 220 patients. There were 120 male and 100 female patients. Mean age of the patients was 55.4±8.2 years. The study analyzed the prescribing patterns of antihypertensive drugs in the cohort of patients with both hypertension and NIDDM. Our study reveals that among patients with both hypertension and NIDDM, ACE inhibitors were the most commonly prescribed drug class, with Enalapril, Lisinopril, and Ramipril being the preferred medications.Conclusion: It is concluded that ACE inhibitors, particularly Enalapril, Lisinopril, and Ramipril, were the predominant antihypertensive drug class prescribed in this patient cohort. This choice is congruent with the well-established benefits of ACE inhibitors in improving blood pressure control and reducing cardiovascular risk, especially in individuals with diabetes.